In vitro responses of ten indica rice genotypes for callus induction - Repalli, Sai Krishna; Baruah, Ananata M; Das, Prasanta K. (Annals of Agricultural Research, 2018)
Genetic modification approach can supplement crop improvement programs in a long run fornutritional and national food security. Generation of rigid and compact embryogenic callus is anessential and primary step for any kind of transformation and genetic modification in rice. Indicarice varieties are known to be recalcitrant to tissue culture regeneration and choosing a suitablegenotype for callus induction has significant importance in rice genetic transformation andregeneration. In this study we had evaluated the callus induction potentials of ten indica rice varieties.Results showed that popular varieties like Swarna (53.3%) and Samba Mahsuri (50%) have highestcallus induction frequencies followed by Nagina-22 (40%). Rest of the genotypes showedcomparatively less callus induction frequency ranging from (20%-36.6%). There were no significantdifferences in callus induction efficiency between the replications and the genotypes. Using Duncan'smultiple ranking the ten genotypes were ranked as per the callus induction efficiency for futuretransformation studies.